Feasibility of thermophilic anaerobic processes for treating waste activated sludge under low HRT and intermittent mixing. (1st October 2017) - Leite, Wanderli; Magnus, Bruna Scandolara; Guimarães, Lorena Bittencourt; Gottardo, Marco; Belli Filho, Paulo
Abstract: Thermophilic anaerobic digestion (AD) arises as an optimized solution for the waste activated sludge (WAS) management. However, there are few feasibility studies using low solids content typically found in the WAS, and that consider uncommon operational conditions such as intermittent mixing and low hydraulic retention time (HRT). In this investigation, a single-stage pilot reactor was used to treat WAS at low HRT (13, 9, 6 and 5 days) and intermittent mixing (withholding mixing 2 h prior feeding). Thermophilic anaerobic digestion (55 °C) was initiated from a mesophilic digester (35 °C) by the one-step startup strategy. Although instabilities on partial alkalinity (1245–3000 mgCaCO3 /L), volatile fatty acids (1774–6421 mg/L acetic acid) and biogas production (0.21–0.09 m 3 /m 3 reactor .d) were observed, methanogenesis started to recover in 18 days. The thermophilic treatment of WAS at 13 and 9 days HRT efficiently converted VS into biogas (22 and 21%, respectively) and achieved high biogas yield (0.24 and 0.22 m 3 /kgVSfed, respectively). Intermittent mixing improved the retention of methanogens inside the reactor and reduced the washout effect even at low HRT (<9 days). The negative thermal balance found was influenced by the low solids content in the WAS (2.1% TS) and by the heat losses from the digester walls. The energy balance and economic analyses demonstrated the feasibility of thermophilic AD of WAS in a hypothetical full-scale system, when the heat energy could be recovered from methane in a scenario of higher solids concentration in the substrate (>5% TS). Highlights: Waste activated sludge was treated at 55 °C under low HRT and intermittent mixing. Methanogenesis started to recover in 18 days after the one-step temperature change. High VS removal (22%) and biogas yield (0.24 m 3 /kgVSfed ) were achieved with 13d HRT. Intermittent mixing compensated the washout phenomena even for the lowest HRT. Methanogens in the bottom sludge kept the CH4 content in biogas higher than 60%.